Laser metal deposition characterization study of metal additive manufacturing repair of rail steel specimens - Nellian, Alagu Subramaniam (2023)
Research on rail steel repair with Stellite 6 powder using a laser metal deposition process was investigated and reported in this study. Rail failures due to excessive wear and other rail head defects can increase the risk of operation and reliability problems in service life. This study examines the deposited material compatibility of a cobalt-based alloy, Stellite 6 with the head-hardened R350HT grade rail steel substrate. Materials characterization work includes metallurgical, wear, and shear properties testing and analysis. Microstructural analysis and hardness measurements of the cross-section from raster scan pattern deposition strategy of Stellite 6 on rail steel substrate surface showed minimal dilution and high hardness of the deposited layer with no presence of defects. Experimental testing of rail wear was conducted using a laboratory ball-on-disc tribometer setup and the wear coefficients for Stellite 6 and rail steel were derived from the wear volume analysis using Archard’s wear model. The material interface bond strength was evaluated from shear testing and analysis to measure the shear interface strength of the metallurgical bond between deposited material on a rail steel substrate.